Occupational Needs of Adolescents with Disabilities: A Case of Rural Community in the Philippines - Lim, Karl Jerick; Nuñez, Deborah; Sarza Jr., Sergio (JPAIR Multidisciplinary Research, 2021)
Occupational needs refer to an individual’s need to engage in meaningful occupations throughout his/her day-to-day life. Certain external factors may influence an adolescent’s occupational need, including socio-economic factors, current health status, cultural beliefs or institutional environment, health education, and medical resources. In third-world countries, occupational needs are apparent and have reduced opportunities to acquire work or participate in leisure participation/exploration for clients who have a physical impairment in the community leading to unsatisfied well-being. In addition, adolescents with disabilities may find it challenging to perform their daily occupations. The researchers aimed to identify the occupational needs of adolescents with disabilities currently attending therapy services in the Argao Community-Based Project. The study utilized a convenience sampling technique and was conducted in a rural community in Argao Cebu with eight participants. The researcher collected data through one-on-one semi-structured interviews. The narratives were then transcribed and analyzed to come up with the top occupational needs of the adolescents. Several themes emerged based on the adolescents’ narratives on their occupational needs.  The themes included: Sustaining Role, Values, Priorities, Essential Occupational Performance, and Belonging to a Group. The researchers found an interdependence between the themes. An occupational therapy program was then proposed to meet the said needs.
Keywords: Social science; Adolescents with special needs; Community-based rehabilitation; Health; Occupational needs; Occupational Therapy; Well-being; and Persons with Disability (PWDs)